Care of Forgiveness in the jurisprudence of Jihad - Abdullah , Luqman (Islamic Sciences Journal, 2023)
ABSTRACT Allah, the Blessed and Exalted be He, has prescribed a solid religion to His Worshippers and guided them on a straight path. This required that this religion has some of the characteristics and features that make it valid for every time and place for all nations of the earth. With Muslims and non-Muslims. There are also many recent researches and studies in this regard, and my share in it was (caring for the aspect of forgiveness in the jurisprudence of jihad), because this topic is of agreat importance in our days, because of what our country and most Islamic countries are experiencing in terms of the internal infighting crisis, and the lack of forgiveness, among the people. This is one of the images of the greatness of Islam in its realism and universality, God Almighty has decreed that all the people of the earth do not believe in all of them, and with the survival of unbelief on earth and with the necessity of communicating the call to all people, the Islamic community is isolated from other societies. The Islamic legislation regulated the relationship of a Muslim with other individuals and societies, and set full controls of it within the Islamic community and outside it.